“We’re the Bottom”: African-American student perceptions of racial order at predominantly White institutions - Coleman, Curtis L. (My University, 2020)
The problem addressed in this study is the lack of awareness of African-American students’ feelings of deficit, attrition, oppression, and negative stereotypes as components contributing to their perception and definition of racial order. This study highlighted the perceptions of racial order through draw-and-write/talk technique by collecting data from 12 African-American undergraduate female students at a Predominantly White Institution. The findings explored the overarching question: How do African-American students perceive and describe racial order at PWI? The participants in this study reported feelings of inferiority, at the bottom within the racial hierarchy, indifference toward others, and isolated themselves as a coping mechanism to avoid racial profiling, stereotyping, and verbal slights. Supported by four components as the essence of racial order, the research focused on the influence of racial order, racial ranking, and the differing perceptions of individual views in contrast to societal norms. Thus, the essence of racial order was summarized into four components e.g., caboose, siloed, inferiority, and transformative. Connecting the discussion to empirical and theoretical literature, this research elucidates justifications for negative feelings, tactics to manage racial order awareness, and aspirations for reformation of racial order.
Keywords: Student affairs services; College Students; Education; African American college students; Universities and colleges